The effects of a CCR3 inhibitor, AXP1275, on allergen‐induced airway responses in adults with mild‐to‐moderate atopic asthma. Issue 4 (13th March 2018) - Gauvreau, G. M.; FitzGerald, J. M.; Boulet, L. P.; Watson, R. M.; Hui, L.; Villineuve, H.; Scime, T. X.; Schlatman, A. R.; Obminski, C.; Kum, J.; Boehme, S.; Ly, T. W.; et al.
Summary: Background: CCR3 is the cognate receptor for major human eosinophil chemoattractants from the eotaxin family of proteins that are elevated in asthma and correlate with disease severity. Objective: This proof‐of‐mechanism study examined the effect of AXP1275, an oral, small‐molecule inhibitor of CCR3, on airway responses to inhaled allergen challenge. Methods: Twenty‐one subjects with mild atopic asthma and documented early and late asthmatic responses to an inhaled aeroallergen completed a randomized double‐blind cross‐over study to compare early and late allergen‐induced asthmatic responses, methacholine PC20, blood and sputum eosinophils and exhaled nitric oxide after 2 weeks of treatment with once‐daily doses of AXP1275 (50 mg) or placebo. Results: There was a significant increase in methacholine PC20 after 12 days of AXP1275 treatment compared to placebo (increase of 0.92 doubling doses versus 0.17 doubling doses, P = .01), but this protection was lost post‐allergen challenge. There was no effect of AXP1275 on allergen‐induced late asthmatic responses, or eosinophils in blood and sputum. The early asthmatic response and exhaled nitric oxide levels were slightly lower with AXP1275, but this did not reach statistical significance. The number of subjects who experienced treatment‐emergent adverse events while receiving AXP1275 was comparable placebo. Conclusions & Clinical Relevance: AXP1275 50 mg administered daily was safe and well tolerated, and there was no difference in the type, severity or frequency of treatment‐emergent adverse events in subjects while receiving AXP1275 compared to placebo. AXP1275 increased the methacholine PC20 ; however, the low and variable exposure to APX1275 over a short treatment period may have contributed to poor efficacy on other outcomes.